The effect of developed nurani module in preconception class to pregnancy planning quality - Nurjasmi, Emi; Qonita Rachmah, M.Sc (Nutr&Diet), Qonita Rachmah., (Opción)
Unplanning pregnancy is a complex condition that could lead to maternal and infant death. Thus, an education to increase couples’ knowledge regarding pregnancy is sufficient. This study aims to evaluate the effectiveness of developed conscience module in the preconception class for Prospective Quality Assurance for the quality of pregnancy planning for childbearing age couples. This was a quasi-experiment study with control group design method. The study was conducted for eight months started instrument trial, module training and design the intervention model. 150 couples from two different regions in Indonesia were assigned as intervention and 150 another couples as control group. The difference before and after intervention was analyze using dependent t-test. After the provision of NURANI module through preconception class, the number of respondents who have a quality pregnancy planning more than 13 indicators were increase up to 100%. There was a significant difference (p <0.005) between the average score of knowledge before and after given preconception class using NURANI module. This study implies the continuance of this module for more preconception class in Indonesia